1989
DOI: 10.4319/lo.1989.34.6.1048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phytoplankton and zooplankton biomass and composition reflected by sedimentation

Abstract: Eight 2-week limnocorral (LC) experiments were performed in Lake Lucerne, Switzerland, during 1982Switzerland, during -1984 to study the effects of biomanipulation. The large zooplankton were removed by 95-pm plankton nets in some LCs and different phosphorus fertilization regimes were applied. The chlorophyll a and sestonic POC and PP concentrations decreased significantly in the presence of crustacean zooplankton, whereas algal biomass was 'less affected. Within the short period of 2 weeks this "top-down"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 42 publications
(45 reference statements)
4
37
1
Order By: Relevance
“…As in marine systems, it has been demonstrated that larger particles contribute more to the sinking flux than do smaller particles (Bloesch and Burgi 1989;Weilenmann et al 1989). However, only recently macroscopic organic aggregates have been described in a lake (Grossart and Simon 1993;Grossart 1995).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…As in marine systems, it has been demonstrated that larger particles contribute more to the sinking flux than do smaller particles (Bloesch and Burgi 1989;Weilenmann et al 1989). However, only recently macroscopic organic aggregates have been described in a lake (Grossart and Simon 1993;Grossart 1995).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Lynch & Shapiro 1981, Hessen et al 1986, Horstedt et al 1988, Mazumder et al 1988. Consequently, sedimentary losses of particulate nutrients tend to increase due to the higher sinking velocities of larger cells (Bloesch & Burgi 1989, Mazumder et al 1989 and Increased contribution of zooplankton fecal material to the settling flux (Bloesch & Burgi 1989). Addition of visually feeding planktivorous fish reduces the numbers of larger herbivores, and leads to a biomass increase of nanoplankton, generally favored by zooplankton grazers (Hessen et al 1986, Mazumder et al 1988, Drenner et al 1989, as well as to a subsequent decline of sedimentation rates and retention of nutrients in the pelagic system (Mazumder et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in both marine and freshwater have found that zooplankton decreases the vertical flux of nutrients and organic matter (e.g., Bathmann et al, 1987;Ayukai & Hattori, 1992;Sarnelle, 1999;Yoshimizu & Urabe, 2002), which has been attributed to a high grazing rate of zooplankton on fecal material, the production of bacteria associated with zooplankton activity, and a high primary production. Other studies have reported an opposite relationship (Honjo & Roman, 1978;Bloesch & Bürgi, 1989;Andreassen et al, 1996;Pilati & Wurtsbaugh, 2003;Pitsch et al, 2012), which is mainly attributed to the presence of a great number of large zooplankton taxa, which produce fecal pellets that sink quickly and resist decomposition (e.g., copepods and euphausiids, Wotton & Malmqvist, 2001). Surprisingly, there have been only a few studies on the effects of zooplankton on the vertical particulate flux in saline lakes (Jellison et al, 1993, Jellison & Melack, 2001) and ponds (Bruce & Imberger, 2009), despite the fact that salinity (density) might have a large (direct and indirect) influence on sedimentation rates.…”
Section: Introductionmentioning
confidence: 87%